1988
DOI: 10.1161/01.str.19.5.631
|View full text |Cite
|
Sign up to set email alerts
|

Altered leukocyte rheology in patients with chronic cerebrovascular disease.

Abstract: Erythrocyte and leukocyte suspensions were prepared from 28 patients with chronic cerebrovascular disease and 30 age-and concomitant disease-matched control subjects. Cell filterability was studied with the new St. George's nitrometer, which can discriminate between initial nitration rate as an erythrocyte parameter and filter clogging as a leukocyte parameter. Compared with control subjects, a significant increase of filter clogging was found in the patients, suggesting decreased deformability or increased ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 15 publications
(5 reference statements)
1
5
0
Order By: Relevance
“…This was first described in 1968 by Ames et al 2 and currently is gaining much interest because it has been hypothesized that leukocyte activation after reperfusion of infarcted myocardium may lead to an extension of the infarcted area. 6 In agreement with other studies 14 - 15 conducted at different time intervals after cerebral infarction, our findings suggest that leukocyte rheology could be an additional relevant variable of the microcirculation during acute cerebral ischemia. Studies in acute cerebral ischemia using rheologic modifying agents (e.g., pentoxifylline and hemodilution) targeted at the RBC have failed to show beneficial effects.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This was first described in 1968 by Ames et al 2 and currently is gaining much interest because it has been hypothesized that leukocyte activation after reperfusion of infarcted myocardium may lead to an extension of the infarcted area. 6 In agreement with other studies 14 - 15 conducted at different time intervals after cerebral infarction, our findings suggest that leukocyte rheology could be an additional relevant variable of the microcirculation during acute cerebral ischemia. Studies in acute cerebral ischemia using rheologic modifying agents (e.g., pentoxifylline and hemodilution) targeted at the RBC have failed to show beneficial effects.…”
Section: Discussionsupporting
confidence: 91%
“…3 - 4 Recently, it has been suggested that alteration of whole blood filterability in vascular diseases is related more to WBC than to the previously held principle of RBC rigidification. 14 ' 15 Our study was designed to evaluate the rheology of blood cell subpopulations (RBC, PNL, MNL) during the acute phase of ischemic stroke (less than 24 hours) introducing two new conditions: observation during the acute phase of ischemia and study of the individual subpopulations. The filtration method used (a technique derived by Lennie et al 11 ) is able to investigate RBC and WBC subpopulations under similar conditions, while it is impossible to study platelet effects and biohumoral influences (i.e., fibrinogen) because of their loss during the separation procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphonuclear (PMN) leukocytes may play an active and significant role in microvascular events (Ernst et aI., 1987;Vernes and Strik, 1988;delZoppo et aI. , 1991;Mori et aI., 1992), parenchy-Surgical preparation had no effect (p � 0.4) on the ability of PMN leukocytes, isolated 24 h after the implantation procedure, to display polarization, 0 2' -production, or r3-g1ucuronidase release when stimulated with human CSa.…”
mentioning
confidence: 99%
“…While a small number of clinical studies on patients recently ex periencing stroke have indicated associative alter ations in leukocyte rheology, (Ernst et aI. , 1987;Vernes and Strik, 1988;Grau et al, 1992), up regulation of the granulocyte 132-intergrin CD18 (Grau et aI. , 1992), and metabolic activation (Grau et aI., 1992), the practical limitations of those stud ies prevent a truly prospective investigation.…”
mentioning
confidence: 99%
“…11 Neutrophil-derived oxygen free radicals 30 -31 and platelet activating factor 29 may also increase vascular permeability. The release of neutrophilderived leukotriene C 4 (LTC 4 ) during ischemic stroke has been verified, and a direct relation between cerebral edema and the level of LTC 4 n has been noted. Although we did not directly measure edema and LTC 4 concentration, it is notable that only the ANAS-treated group did not experience a rise in ICP, which, in the absence of hemorrhage, suggests a reduction in edema formation.…”
Section: Discussionmentioning
confidence: 97%